Species- and Tissue-Specific Variations in Cholesterol Content among Wild and Domesticated Birds in Nsukka, Nigeria (Nigerian Journal of Physiological Sciences, 2025)
Avian species exhibit variations in adaptive features, including differences in lipid metabolism, which are essential for successful survival and reproduction in unique habitats. However, there is a lack of information on species- and tissue-specific variations in cholesterol metabolism among avian species living in similar habitats. This study aimed to investigate potential variations in tissue cholesterol levels in wild (Corvus albus, Passeriformes; and Coturnix coturnix, Galliformes) and domesticated (Gallus gallus domesticus, Galliformes, both local and exotic breeds) avian species found in Nsukka, Nigeria. These species have diverse diets and behaviours. Tissues from the brain, liver, gizzard, heart, and breast muscle were dissected and used for total lipid extraction and cholesterol quantification. The results showed significant species- and tissue-specific differences in cholesterol levels among the examined birds (One-way ANOVA, p < 0.001). Moreover, the brain and liver had notably higher cholesterol content compared to other tissues (One-way ANOVA, p < 0.001 in most cases). Lastly, multiple comparisons showed that domesticated species generally exhibited higher cholesterol levels than wild species. These findings support the hypothesis of species- and tissue-specific differences in cholesterol metabolism in avian species inhabiting similar environments but differing in diets and behaviors.